If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 6 = 0.50(2x + -8) Reorder the terms: 6 + 7x = 0.50(2x + -8) Reorder the terms: 6 + 7x = 0.50(-8 + 2x) 6 + 7x = (-8 * 0.50 + 2x * 0.50) 6 + 7x = (-4 + 1x) Solving 6 + 7x = -4 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6 + 7x + -1x = -4 + 1x + -1x Combine like terms: 7x + -1x = 6x 6 + 6x = -4 + 1x + -1x Combine like terms: 1x + -1x = 0 6 + 6x = -4 + 0 6 + 6x = -4 Add '-6' to each side of the equation. 6 + -6 + 6x = -4 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = -4 + -6 6x = -4 + -6 Combine like terms: -4 + -6 = -10 6x = -10 Divide each side by '6'. x = -1.666666667 Simplifying x = -1.666666667
| 11(x-4)=60 | | 8(x-4)=60 | | 8(63-y)+4y=254 | | (8/7)x-8=6x-4y | | 12-(3x-7)=4-x | | 0=x+8 | | 0.8x=320 | | 3(5x-1)-14x=4 | | 14=3+x | | -36-9y+18=-34y+12+15y | | 4s-1=2-2s | | 10(x-4)=60 | | -a+7=17+3a-4 | | x+3y=80 | | 15+216-315-16= | | 4(y-7)/3=-2y | | -8+7x+9=3x-43 | | 0.4z+0.7=-3.5-1.7z | | 5X+4Y+z=200 | | -4(x-5)+2=22 | | 9+(2x+5)=3(2x+4) | | 1.2+0.3x=0.5x-3.2 | | -9x^4=-48x^2+64 | | 0.5x-2+5= | | 14-7r=6-3r | | 19-3x=5x+3 | | 1x-2=-1 | | 2x-2=3x-1 | | 16x-10=6x+40 | | 5.4x-1=4.4x+9 | | (7/6)x+7=4 | | 16x+27=15x+18 |